2009
DOI: 10.1007/s10029-009-0480-7
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of inguinal hernioplasty on testicular perfusion and sexual function

Abstract: Inguinal hernia impaired testicular perfusion that improved postoperatively. Lichtenstein tension-free hernioplasty improved sexual function and generic quality of life without adverse mesh effects on testicular volume or perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 36 publications
2
21
1
1
Order By: Relevance
“…Improved sexual function (although not studied in relation to pain) has been observed by others too. Ertan et al [4] and El-Awady and Elkholy [5] reported a significant recovery of sexual function 3 months after open anterior mesh repair, with 85% of patients improving their IIEF scores [4], while Zieren et al [2] observed a decline of ''potency or orgasm disorders'' after Plug and Patch repair from 23.2 to 16.1% postoperatively.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Improved sexual function (although not studied in relation to pain) has been observed by others too. Ertan et al [4] and El-Awady and Elkholy [5] reported a significant recovery of sexual function 3 months after open anterior mesh repair, with 85% of patients improving their IIEF scores [4], while Zieren et al [2] observed a decline of ''potency or orgasm disorders'' after Plug and Patch repair from 23.2 to 16.1% postoperatively.…”
Section: Discussionmentioning
confidence: 96%
“…The preoperative presence of painful sexual activity or other chronic pain was predictive of postoperative complaints. Few studies have dealt with sexual function after inguinal hernia repair, merely focusing on general sexual function (such as erectile disorders) [2,5,9] and not so much on pain during sexual activity and pain-related impairment of sexual function [6,7].To our knowledge, this is the first study that evaluates the incidence of painful sexual activity and impairment of sexual function before and after endoscopic totally extraperitoneal (TEP) hernia repair.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thirty-two studies (40%) had a validated assessment of both PI and QOL [11,14,19,20,22,24,29,31,34,38,40,41,43,45,48,53,54,56,58,60,62,65,67,73,74,76,84,86,87,88,89,90]; in 33 (41%) and 3 (4%) of the studies, respectively, there was only a validated assessment of PI [8,10,13,17,21,23,25,26,28,30,33,35,36,42,44,47,49,50,52,59,61,63,69,71,77,78,80,81,82,83,85] or QOL [46,51,57]. …”
Section: Resultsmentioning
confidence: 99%
“…In the other 49 studies (61%), a total of 22 different definitions of CPIP were identified. Almost half (n = 23) of these studies applied the definition provided by the IASP, which is ‘chronic pain is pain that persists beyond three months post-operatively' [39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62]. The remaining half (n = 26) used multiple definitions of CPIP, which can be categorized and summarized as follows.…”
Section: Resultsmentioning
confidence: 99%